WE NEED TO TALK ABOUT SO-CALLED GROWING UP MILKS - Dryelle Oliveira Dias Leão; Muriel Gubert (Universidade do Estado do Rio de Janeiro, 2019)
Industry is constantly looking to innovate and launch new products to attract consumers. In this context, growing up milk was launched. This product with a mixture of at least 51% milk base (milk or dairy products) with other food products, which according to the manufacturers is aimed at children from one years old to pre-school age. There are 13 different types of these mixtures on the Brazilian market. Similar packaging can confuse caregivers, who may believe these compounds are substitutes, equivalents, or follow-up to infant formulas at a reduced cost. They are often promoted commercially with giveaways and discounts on multiple purchases or combos and are heavily promoted on social media. Their labels advertise that they contain essential oils, fiber, immunonutrients, vitamins, and minerals, which may lead consumers to think that the product alone provides everything the child needs for this age, despite being an ultra-processed product, not recommended for consumption by this child. As they are new products in the market, they still are still not regulated by the Brazilian Standard for Commercialization of Food for Infants and Children in Early Childhood, Nipples, Pacifiers, and Feeding Bottles, today Law No. 11,265/2006 and Decree No. 9,579/2018. The suggestion is that these mixtures should be included in the legislation, with marketing controlled within the scope of the law, as well as the creation of rules to restrict the abusive advertising of these and other products for children between one and three years old. DOI: 10.12957/demetra.2019.43609